Theory of Plastic Mechanism Control for MRF–EBF dual systems: Closed form solution. (1st July 2016) - Montuori, Rosario; Nastri, Elide; Piluso, Vincenzo
Highlights: A design methodology aiming to assure a collapse mechanism of global type for MRF–EBF dual systems is reported. This methodology called Theory of Plastic Mechanism Control (TPMC) is extended to the case of Moment Resisting Frames–Eccentrically Braced Frames (MRF–EBF) dual systems. A number of MRF–EBF dual systems have been designed by TPMC and EC8 and their performances have been evaluated by means of push-over analyses. Abstract: In this paper, the closed form solution of the Theory of Plastic Mechanism Control (TPMC) is extended to the case of Moment Resisting Frames–Eccentrically Braced Frames (MRF–EBF) dual systems. As it is known, Eurocode 8 does not provide any specific design criterion regarding such structural typology, so that practitioners commonly carry out the design process by combining the design rules suggested for simple MRFs and EBFs. Therefore, the aim of this work is to provide a complete and exhaustive design procedure for MRF–EBF dual systems, considering all the brace configurations commonly adopted and with the goal of assuring the development of a collapse mechanism of global type. The design procedure to assure this ambitious design goal is based on TPMC whose aim is to derive the column sections required to assure the desired collapse mechanism starting from the knowledge of the dissipative zones. In order to point out the accuracy of the proposed design approach and the differences between itself and Eurocode 8, a number of MRF–EBF dual systems have been designed and their performances have been evaluated by means of push-over analyses.